2017
DOI: 10.3390/rs9060598
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Site-Specific and Generic Spatial Models of Aboveground Forest Biomass Based on Landsat Time-Series and LiDAR Strip Samples in the Eastern USA

Abstract: Large-area assessment of aboveground tree biomass (AGB) to inform regional or national forest monitoring programs can be efficiently carried out by combining remotely sensed data and field sample measurements through a generic statistical model, in contrast to site-specific models. We integrated forest inventory plot data with spatial predictors from Landsat time-series imagery and LiDAR strip samples at four sites across the eastern USA-Minnesota (MN), Maine (ME), Pennsylvania-New Jersey (PANJ) and South Caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 77 publications
1
32
1
1
Order By: Relevance
“…Among the selected variables from both LiDAR and Landsat data, LiDAR metrics were much more influential to stand basal area and associated AGB than Landsat variables. This finding is consistent with previous studies (Deo et al 2017a(Deo et al , 2017b. Nevertheless, we found that Landsat variables alone can also be used to replace stand basal area to predict AGB in the study region although with higher RMSE (9.34-12 Mg ha −1 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the selected variables from both LiDAR and Landsat data, LiDAR metrics were much more influential to stand basal area and associated AGB than Landsat variables. This finding is consistent with previous studies (Deo et al 2017a(Deo et al , 2017b. Nevertheless, we found that Landsat variables alone can also be used to replace stand basal area to predict AGB in the study region although with higher RMSE (9.34-12 Mg ha −1 ).…”
Section: Discussionsupporting
confidence: 93%
“…The average width of the strips was about 1.2 km. The LiDAR datasets were summarized to obtain the grid metrics for canopy cover and vertical strata density as defined in Deo et al (2017aDeo et al ( , 2017b. In addition, the Landsat time-series data were acquired by Landsat-5 Thematic Mapper (TM) and Landsat-8 Operational Land Imager (OLI) sensors at the peak of the growing seasons (July-September) from 1984-2015.…”
Section: Lidar and Landsat Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Airborne laser scanning (ALS) is a widely used LiDAR technology in forestry, which has a unique advantage in 3D terrain and forest height detection. It can quickly and accurately obtain a digital surface model (DSM) and forest height information for forested land [4,5]. According to the statistics, single-tree detection algorithms that use active RS data, such as ALS, have grown rapidly in recent years, accounting for 80% of the total increase in RS area, at the same time, those algorithms using passive data or a fusion of passive and active data accounts for 8% and 12% respectively [6].…”
Section: Introductionmentioning
confidence: 99%
“…As the principal part of terrestrial ecosystems, forest ecosystems hold approximately 80% of the terrestrial aboveground and below-ground biomass, and play very important roles in the global carbon cycle and climate change [1][2][3]. Since the temperate and boreal forests play a crucial role as atmospheric CO2 sinks, more attention has been paid to climatic warming in mid-and high-latitudes…”
Section: Introductionmentioning
confidence: 99%